Development of Learning Method Based on Triarchy Intelligence for The Arabic Writing Skills of Students Class VII MTs - Ike Fitriana Saraswati; Zukhaira Zukhaira (Universitas Muhammadiyah Enrekang, 2023)
This research is driven by the challenges faced in Arabic writing skill instruction, where the performance has been suboptimal. One of the notable repercussions of these challenges is the students' reduced capacity to generate innovative ideas in their Arabic writing, subsequently hampering their critical thinking abilities in composing essays. In the realm of Arabic writing instruction, students must undergo a multistep process, encompassing word/sentence analysis, idea generation, and essay composition. Hence, there arises a need for a methodology capable of stimulating students' capacity for analytical, creative, and practical thinking. The research inquiries in this investigation encompass: (1) the assessment of teachers' and students' requirements concerning the adoption of a learning approach based on the Triarchy of Intelligence for enhancing Arabic writing skills among seventh-grade MTs students, (2) the development of a prototype for a Triarchy of Intelligence-based learning method for bolstering Arabic writing skills among seventh-grade MTs students, and (3) the expert and teacher validation, along with subsequent revisions of the prototype's design for a learning method rooted in the Triarchy of Intelligence, intended to enhance Arabic writing skills among seventh-grade MTs students. This research utilizes qualitative research methods, employing a research and development design. The research phases covered in this study only progress up to the fifth stage out of ten planned stages, which include the identification of potential and problems, data collection, product design, design validation, and design revision. The outcomes of this research can be summarized as follows. Firstly, both teachers and students express a desire to implement a development of learning methods based on the Triarchy of Intelligence to enhance Arabic writing skills among seventh-grade MTs students. Secondly, the prototype of this learning method encompasses the rationale behind its creation, key competencies and performance indicators for Arabic writing skills in the second semester of the seventh grade, instructional steps, and assessment criteria. Lastly, the evaluation of the material/content's appropriateness yields a score of 91.9, while the appropriateness of the presentation receives a score of 94.4. The language aspect is rated at 45.66, and the method's feasibility aspect attains a score of 104.48. Consequently, the overall assessment of this learning method stands at 336.44, classified as